Carotid endarterectomy outcomes according to anesthesia method: General anesthesia or regional anesthesia? - Fehim Can Sevil; Serkan Gume; Mehmet Tort; Necip Becit (Turkish Journal of Vascular Surgery)
Aim: Surgical strategies in carotid endarterectomy (CEA) vary according to the method of anesthesia, neurological monitoring, shunt use, and closure methods, and the gold standard method has not yet been determined. In this study, we aimed to analyze the superiority and feasibility of CEA under general anesthesia and regional anesthesia. Material and Methods: Demographic characteristics, operative information and follow-up results of 237 patients who underwent CEA between January 2015 and June 2020, 165 patients under regional anesthesia (RA: Group 1) and 72 under general anesthesia (GA: Group 2), were retrospectively analyzed. In Group 1, carotid shunt was placed in patients with a negative awake test (n: 21, 12.7%) and in Group 2 carotid shunt was placed in all cases. Results: There was no statistically significant difference in postoperative stroke, transient ischemic attack (TIA) and cardiovascular mortality (p: 0.48; p: 0.30; p: 0.63, respectively). Although the operation and clamp time were shorter in Group 1, no significant difference was observed (97.93±11.02 min, 101.46±9.49 min p: 0.23; 19.60±5.62 min, 25.62±7.47 min p: 0.24, respectively). The duration of intensive care unit (ICU) stay was shorter and statistically significant in Group 1. (p: 0.003). There was no significant difference for restenosis rates (p: 0.34). Conclusion: There was no significant increase in postoperative complications in the RA group compared to the GA group despite shunting according to the awake test. Also, patients who underwent RA stayed in ICU for a shorter period of time. CEA can be performed under both GA and RA with similar complication rates. [Turk J Vasc Surg 2024; 33(2.000): 71-77]